Early-Onset Spinal Deformity in Neurofibromatosis Type 1: Natural History, Treatment, and Imaging Surveillance. Issue 7 (July 2021) - Marrache, Majd; Suresh, Krishna V.; Miller, Daniel J.; Hwang, Steven; Schorry, Elizabeth K.; Rios, Jonathan J.; Sponseller, Paul D.
Abstract : Early-onset scoliosis (EOS) or kyphosis is common in patients with neurofibromatosis (NF) and is characterized by rapid progression of deformity. Traditional growing rods provide good functional and deformity outcomes in patients with NF and EOS; magnetically controlled growing rods (MCGRs) also provide good deformity correction, although high rates of revision have been reported after their use. Among patients with NF type 1 (NF1), morphologic characteristics of the spinal deformity are different in those with paraspinal neurofibromas than in those without paraspinal tumors. Patients with NF1 are at low risk for developing malignant peripheral nerve sheath tumors during childhood (<1%) and their lifetime (8% to 12%), and routine imaging surveillance for malignancy in the absence of symptoms should be clinically directed. Further investigation is needed to standardize screening for EOS in children with NF1 and to develop guidelines for ideal imaging modalities, including their frequency and a timeline.